Anharmonic enhancement of superconductivity in metallic molecular Cmca − 4 hydrogen at high pressure: a first-principles study. (7th October 2016) - Borinaga, Miguel; Riego, P; Leonardo, A; Calandra, Matteo; Mauri, Francesco; Bergara, Aitor; Errea, Ion
Abstract: First-principles calculations based on density-functional theory including anharmonicity within the variational stochastic self-consistent harmonic approximation are applied to understand how the quantum character of the proton affects the candidate metallic molecular Cmca   −  4 structure of hydrogen in the 400–450 GPa pressure range, where metallization of hydrogen is expected to occur. Anharmonic effects, which become crucial due to the zero-point motion, have a large impact on the hydrogen molecules by increasing the intramolecular distance by approximately a 6%. This induces two new electron pockets at the Fermi surface opening new scattering channels for the electron–phonon interaction. Consequently, the electron–phonon coupling constant and the superconducting critical temperature are approximately doubled by anharmonicity and Cmca   −  4 hydrogen becomes a superconductor above 200 K in all the studied pressure range. Contrary to many superconducting hydrides, where anharmoncity tends to lower the superconducting critical temperature, our results show that it can enhance superconductivity in molecular hydrogen.